Plasma macrophage colony-stimulating factor levels during cardiopulmonary bypass with extracorporeal circulation - Y. Denizot; P. Fixe; E. Cornu; N. Nathan (Mediators of Inflammation)
Leukocytosis and thrombocytopenia occur during cardiopulmonary bypass (CPB) with extracorporeal circulation (ECC). Elevated circulating concentrations of macrophage colony-stimulating factor (M-CSF) are reported during thrombocytopenia and leukopenia of different origins. We have assessed M-CSF concentrations in 40 patients undergoing CPB with ECC. Plasma M-CSF concentrations were stable during ECC and increased at the 6th (7.3 ± 0.7 IU/μg protein) and 24th (8.6 ± 0.8 IU/μg protein) postoperative hour compared with pre-ECC values (4.9 ± 0.5 IU/μg protein). A deep thrombocytopenia was found during ECC and until the 24th postoperative hour. A drop of leukocyte counts was found during ECC followed by an increase after ECC weaning. While no correlation was found between M-CSF concentrations and the leukocyte counts, M-CSF values were positively correlated with platelet counts only before and during ECC. Thus, M-CSF is not implicated in the thrombocytopenia and the leukopenia generated during CPB with ECC. However the elevated levels of M-CSFa few hours after the end of ECC might play a role in the inflammatory process often observed after CPB.